Media organisation and production - Cottle, Simon, 1956- (Media in focus., 2003)
Drawing on the work of international contributors Media Organization and Production examines a wide range of global-local media organizations and the production of different mediums and genres. Following the editor's introduction which sets out the principal differences of approach and defining debates, chapters address: - transnational and national, commercial and public service corporations; - international film and TV co-productions; - children's television news production, the historical development of 'liveness' on radio, and music journalism; - the politics and organizational forms of al.